From the history of VU Faculty of Mathematics and Informatics: the development of admission to mathematical studies - Belovas, Igoris (Lietuvos matematikos rinkinys, 2025)
Based on primary source data, the paper examines the development of admissions to mathematical studies at Vilnius University's Faculty of Physics and Mathematics (1945–1965), Faculty of Mathematics and Mechanics (1966–1977), and Faculty of Mathematics (1978–1990).
Keywords: history of Vilnius University; history of the Faculty of Mathematics and Informatics; admission statistics